2004
DOI: 10.1111/j.1365-2036.2004.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

The Visceral Sensitivity Index: development and validation of a gastrointestinal symptom‐specific anxiety scale

Abstract: SUMMARYBackground: Anxiety related to gastrointestinal sensations, symptoms or the contexts in which these may occur is thought to play a significant role in the pathophysiology as well as in the health outcomes of patients with irritable bowel syndrome. Aim: To develop a valid and reliable psychometric instrument that measures gastrointestinal symptomspecific anxiety. Methods: External and internal expert panels as well as a patient focus group evaluated a large pool of potential item stems gathered from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
409
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(442 citation statements)
references
References 34 publications
20
409
3
10
Order By: Relevance
“…The present findings on how fear towards innocuous gastrointestinal sensations can come about through an associative learning process is relevant for any gastrointestinal disorder but for FGID in particular, as many of those patients are characterized by excessive distress and fear towards certain types of gastrointestinal sensations 4 . Recently, we have found that associative learning leading to gastrointestinal sensations does not only cause emotional distress, but also alters perceptual thresholds for those gastrointestinal sensations 13 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The present findings on how fear towards innocuous gastrointestinal sensations can come about through an associative learning process is relevant for any gastrointestinal disorder but for FGID in particular, as many of those patients are characterized by excessive distress and fear towards certain types of gastrointestinal sensations 4 . Recently, we have found that associative learning leading to gastrointestinal sensations does not only cause emotional distress, but also alters perceptual thresholds for those gastrointestinal sensations 13 .…”
Section: Discussionmentioning
confidence: 81%
“…Gastrointestinal symptom-specific fear, the apprehension of specific visceral sensations, is one of the most important cognitive-affective processes in this context 4,5 as it is associated with symptom severity and quality of life in FGID, specifically in irritable bowel syndrome (IBS) 6 . Furthermore, decreases in gastrointestinal symptom-specific fear mediates the effect of exposure-based cognitive behavioral therapy on IBS symptoms 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Visceral Sensitivity Index (VSI) is a reliable, valid measure of gastrointestinal symptom-specific anxiety [100]. It has 15 items assessing anxiety related to gastrointestinal sensations that are rated on a 6- point scale from strongly agree to strongly disagree and takes less than 5 minutes to complete.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…In a study of 234 patients in which the impact of a variety of physical and psychological variables was investigated, GSA was the most robust predictor of QOL impairment 36 . A validated tool for measuring GSA is the 15-item Visceral Sensitivity Index 15 , which assesses worry, hypervigilance, and heightened focus on GI sensations. Items are rated on a scale from 0 (strongly disagree) to 5 (strongly agree).…”
Section: Gi-specific Anxiety (Gsa)mentioning
confidence: 99%
“…Although stress also affects gut function in healthy individuals, patients with IBS demonstrate greater stress sensitivity with regard to gut motility, visceral perception, and hypothalamic-pituitary-adrenal axis hormone levels 14 . One central process is GI symptom-specific anxiety, which is regarded as a prominent endogenous stressor that can perpetuate IBS symptoms even in the absence of external stress 15 .…”
Section: Introductionmentioning
confidence: 99%